Genetic influence on the associations between IGF-I and glucose metabolism in a cohort of elderly twins. Issue 2 (February 2018) - Jensen, Rikke Beck; Thankamony, Ajay; Holst, Klaus K; Janssen, Joseph A M J L; Juul, Anders; Dunger, David; Poulsen, Pernille; Scheike, Thomas
Abstract : Objective: IGF-I may be a marker of later metabolic and cardiovascular disease. The interactions between IGF-I and glucose metabolism are multifactorial, and there is potential confounding from several secondary effects. In this study, we examined the interaction between IGF-I and glucose metabolism in a large cohort of clinically well-characterized elderly twins. Design: A total of 303 twin pairs of the same gender (606 twins) were included in the study; 125 monozygotic and 178 dizygotic twin pairs. Methods: A clinical examination including a standard oral glucose tolerance test (OGTT) and anthropometric measurements was performed. Results: The heritability estimates were high for IGF-I and IGFBP-3 (h2 : 0.65 (95% CI: 0.55–0.74) and 0.71 (0.48–0.94), respectively) and for insulin secretion (h2  = 0.56, P  < 0.0001), whereas the heritability estimates for insulin sensitivity were low (h2  = 0.14, P  = 0.11). In a multiple regression analysis (adjusting for age, gender and twin status), there was a negative association between IGF-I and insulin sensitivity (B: −0.13, SE 0.03, P  < 0.0001) and IGF-I and disposition index (B: −0.05, SE 0.02, P  < 0.001) in the entire cohort of 606 twins. The associations between IGF-I and both DI and HOMA-S did not differ between the DZ and MZ twins. Forty-five twin pairs were discordant for T2D, but the discordant twins had similar concentrations of IGF-I or IGFBP-3. Conclusions: There was a high heritability for IGF-I and IGFBP-3, but a low heritability for insulin secretion and insulin sensitivity in a group of elderly twins. In addition, we found a strong negative relationship between IGF-I and insulin sensitivity, which did not seem to be strongly genetically determined.